Pengaruh Pemberian Minyak Zaitun Terhadap Penurunan Derajat Ruam Popok Pada Batita - Syifa Anisa; Rita Riyanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background : Based on data from the Indonesian Ministry of Health in 2018 the incidence of diaper rash in Indonesia alone has reached 7-35%, which affects male and female infants less than three years old. This is because there is a lot of interest in using disposable or disposable diapers. One of the treatments thatl can bel used tol treat diaperl rash in babies isl to use olive loil. Olive oil contains many active compounds that are beneficiall for thel skin, repairingl damaged skinl cells asl antioxidants neutralizingl free lradicals, reducing rednessl on thel skin andl can protectl the skinl from lirritation. Purpose : This studyl aims to analyzel the effectl of giving olivel oil to reduce thel degree ofl diaper rashl in toddlers. Research Methods: This type of research is pre-experimental using a one group pretest-posttest design with a total sample of 22 respondents. Results: The results of the Wilcoxon test before and after being given treatment showed a p value of 0.000 <0.05, meaning that there was a positive effect of giving olive oil on reducing the degree of diaper rash in toddlers.